Innovation in Public Service Governance at Prima Husada Sengkang Hospital Tempe District Wajo Regency - Besse Herlina; Jamal Qadar; Irwana Irwana (International Journal of Social Science and Humanity, 2026)
This study to analyze innovation in public service governance and identify determinant factors that influence its implementation at Prima Husada Sengkang Hospital, Tempe District, Wajo Regency. This study uses a qualitative research method with a descriptive approach. The research informants consisted of 5 people: doctors, nurses, administrative staff, patients, and patients' families. Data collection techniques were carried out through interviews and documentation. Data analysis used the Miles and Huberman model which includes data reduction, data presentation, data verification, and conclusion drawing. The results show that public service governance at Prima Husada Sengkang Hospital has implemented the principles of transparency, accountability, responsiveness, and effectiveness. Supporting factors for innovation are the existence of good resolution and accommodation in resolving patient problems or complaints supported by effective communication and coordination. Meanwhile, inhibiting factors come from societal dynamics in the form of increasing public demands for service quality, expectations of cooperation with BPJS, improvements in service facilities, timeliness of doctor services, and network constraints that affect the use of SIM RS.